Identification and characterisation of novel human dendritic cell progenitors - See, Peter Chi Ee (2016)
Dendritic cells (DCs) are professional antigen presenting cells that initiate the immune response. They are heterogeneous and are broadly classified into three groups – two major subsets of conventional DCs (cDC) named cDC1 and cDC2, and plasmacytoid DC (pDC). Each subset has unique transcription factor dependency, and specialised functions. DCs are derived from a unique lineage of DC-restricted progenitors that are until now not yet fully characterised. Currently, there are limited genetic lineage fate mapping mice models available to track the development of DCs in steady state and inflammation. We have identified Uroplakin-1b (Upk1b) as uniquely expressed in DC-restricted progenitors. Surprisingly, this molecule is also expressed in microglia. We developed a fate mapping Upk1b-cre mouse, which was crossed to Rosa-YFP reporter mouse to generate Upk1b-cre:Rosa YFP. Contrary to our expectations, we observed low recombination in DC-restricted progenitors and DC subsets. However, the recombination level in the microglia was close to 80% in young adults, suggesting that it may be a useful model for microglial research. Upk1b is conserved across species and may serve as a potential marker to identify DC-restricted progenitors in humans.